2015
DOI: 10.18869/acadpub.vacres.2.3.9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of AbOmpA type-1 as immunogenic target for therapeutic interventions against MDR Acinetobacter baumannii infection

Abstract: Introduction: Acinetobacter baumannii is associated with hospital-acquired infections. Outer membrane protein A of A.baumannii (AbOmpA) is a well-characterized virulence factor which has important roles in pathogenesis of this bacterium. Methods: Based on our PCR-sequencing of ompA gene in the clinical isolates, AbOmpA protein can be categorized into two types, named here type-1 and type-2. We are performed in silico analyses on beta-barrel domain of AbOmpA such as sequence alignments, prediction of 3D modelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 32 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…A soluble and stable globular domain in C-terminal of the protein interacts with the peptidoglycan layer in the periplasmic space and it is required for the integrity of the cell [36]. Multiple sequence alignments of beta-barrel domain showed L4 was conserved while L1, L3, and L2 had more amino acid changes [29]. The extracellular loops are functional and dynamic regions of this protein which could be involved in adherence, invasiveness, biofilm formation, apoptosis, immune stimulation, iron metabolism and serum resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A soluble and stable globular domain in C-terminal of the protein interacts with the peptidoglycan layer in the periplasmic space and it is required for the integrity of the cell [36]. Multiple sequence alignments of beta-barrel domain showed L4 was conserved while L1, L3, and L2 had more amino acid changes [29]. The extracellular loops are functional and dynamic regions of this protein which could be involved in adherence, invasiveness, biofilm formation, apoptosis, immune stimulation, iron metabolism and serum resistance.…”
Section: Discussionmentioning
confidence: 99%
“…These following procedures were performed only for AbOmpA and PKF, as promising vaccine targets. Data have shown that the beta-barrel domain of AbOmpA is similar to beta-barrel domain of Klebsiella pneumoniae OmpA (PDB accession number is 2K0L) [29]. This domain has 4 extracellular loops.…”
Section: D Modeling and B Cell Epitope Predictionsmentioning
confidence: 99%